2021
DOI: 10.1002/jcla.23816
|View full text |Cite
|
Sign up to set email alerts
|

Age‐stratified and gender‐specific reference intervals of six tumor markers panel of lung cancer: A geographic‐based multicenter study in China

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…In addition, almost all cardiometabolic risk factors were significantly associated with high serum CEA levels. Similar to previous studies, CEA levels did not only increase in CRC but were also higher in some chronic diseases, especially CVDs, MetS, and diabetes (17,19,22). This finding implies that clinicians can use serum CEA as a useful biomarker for the early detection of cardiometabolic risks and unhealthy lifestyles rather than solely as a tumor marker for CRC.…”
Section: Serum Cea Can Be Used For the Early Detection Of Cardiometab...supporting
confidence: 88%
See 3 more Smart Citations
“…In addition, almost all cardiometabolic risk factors were significantly associated with high serum CEA levels. Similar to previous studies, CEA levels did not only increase in CRC but were also higher in some chronic diseases, especially CVDs, MetS, and diabetes (17,19,22). This finding implies that clinicians can use serum CEA as a useful biomarker for the early detection of cardiometabolic risks and unhealthy lifestyles rather than solely as a tumor marker for CRC.…”
Section: Serum Cea Can Be Used For the Early Detection Of Cardiometab...supporting
confidence: 88%
“…Carcinoembryonic antigen (CEA, ng/mL) was measured by electrochemiluminescence immunoassay (ECLIA) on Roche Cobas e801 analyzer. Instead of using reference intervals published in manufacturers' package inserts, we used CEA ≥ 3.0 ng/mL as the cut-off value for the high serum level group based on previous studies, considering age, sex, and smoking habits (18,22,26).…”
Section: Carcinoembryonic Antigenmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific reasons are as follows: ProGrp is a gastrointestinal hormone commonly found in various neuroendocrine-derived tumours, and clinical studies have found that it has high sensitivity and specificity for the diagnosis of small-cell lung cancer and can be used as a marker for small-cell lung cancer, which helps in the diagnosis and clinical treatment of small-cell lung cancer disease [ 12 ].CEA is an acidic glycoprotein in intestinal cancer, mainly in the embryonic stage by the small intestine and the liver. It is a broad-spectrum tumour marker and its level increases dramatically after the development of many tumours [ 13 ].CA211 is mainly found in the cytoplasm of tumour cells and can be released into the blood when tumour cells are necrotic or lysed, which is useful for the diagnosis and treatment of squamous carcinoma [ 14 ].NSE is an acidic protease that is found in neural tissue and the neuroendocrine system and mainly acts in the glycolytic pathway [ 15 ]. It was found that small-cell lung cancer can secrete NSE and release it into the blood, resulting in elevated levels, so monitoring SE is useful in the diagnosis and treatment of small-cell lung cancer, but the presence of NSE in red blood cells can lead to falsely elevated results [ 16 ].…”
Section: Discussionmentioning
confidence: 99%